Analisis Corak Pemikiran Fikih K.H. Lanre Said Al-Bugisi - Syandri, Syandri; Kadir, Ilham; Azwar Iskandar (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2021)
This research aims to find out the pattern of Islamic jurisprudence’s thought and the ijtihad method of K.H. Lanre Said. This research is a qualitative descriptive using data related to Islamic jurisprudence’s thought of K.H. Lanre Said. The results showed that the knowledge of K.H. Lanre Said in the field of Islamic jurisprudence is enough high. Although it looks practical and simple, his ability to decipher the opinions of scholars is very good especially in the description of evidence derived from hadith. He expressed the opinions of the scholars then conclude them, although in several problems he did not choose one opinion of the scholars even made his own opinion. The Islamic jurisprudence concept in his mind is enough dynamic because he wrote many laws in jurisprudence problems relating to the law of ablution (taharah) until corpse (janazah) and other issues that are widely questioned and often occur in the community. In general, it can be said that the pattern of K.H. Lanre Said’s thought does not depend on just one sect (mazhab), even he encourage the freedom of embracing the spect.